1971
DOI: 10.1079/bjn19710020
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia in the large intestine of herbivores

Abstract: 1. The object was toinvestigate the importance of urea a source of ammonia in the large intestine of herbivores. Urea was present in small intestinal contents of slaughtered horses in concentrations similar to those in blood but, in the small intestine of salughtered sheep, the urea was less than in blooc.2. There was little ammonia in small intestinal contents of slaughtered horses but consider-able ammonia was present in small intestinal contents of slaughtered sheep. The ammonia in small intestinal contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 16 publications
4
12
1
Order By: Relevance
“…Our study clearly showed that the amount of urea-N secreted into the caecum and colon was related to the blood urea level, which is in agreement with results of Hecker (1971), Nolan and Leng (1972), Engelhardt et al (1984) and Żebrowska and Kowalczyk (1991) indicating that a substantial quantity of plasma urea enters the post-ruminal part of digestive tract of sheep. Hecker (1971) demonstrated a close correlation between urea concentration in blood and ammonia, originating from endogenous urea, in the ileum and colon of sheep.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study clearly showed that the amount of urea-N secreted into the caecum and colon was related to the blood urea level, which is in agreement with results of Hecker (1971), Nolan and Leng (1972), Engelhardt et al (1984) and Żebrowska and Kowalczyk (1991) indicating that a substantial quantity of plasma urea enters the post-ruminal part of digestive tract of sheep. Hecker (1971) demonstrated a close correlation between urea concentration in blood and ammonia, originating from endogenous urea, in the ileum and colon of sheep.…”
Section: Discussionsupporting
confidence: 80%
“…Hecker (1971) demonstrated a close correlation between urea concentration in blood and ammonia, originating from endogenous urea, in the ileum and colon of sheep. Engelhardt et al (1984) also found a high positive correlation between urea level in blood and urea secretion into the colon but the amount of urea secreted was low (0.1 to 0.3 mmol/h) suggesting that permeability of the colon epithelium for urea is rather low.…”
Section: Discussionmentioning
confidence: 99%
“…After the administration of 706 mg of labelled "N urea into the cecum, the appearance of isotope in urine, feces, blood, rumen and duodenum content was investigated during 7 days. (Boda et al 1976) and the relatively high concentration of urea in their chymus (Hecker 1971) This follows from the findings of similar '5N levels in both total and protein nitrogen in duooenum content.…”
supporting
confidence: 57%
“…Several studies on sheep and cattle have reported that the retention time of chyme in the large intestine is shorter than that in the rumen 46 . However, the segment of the large intestine is narrow and long, and its absorption capacity per unit volume may exceed that of the other intestinal regions 7 .…”
Section: Introductionmentioning
confidence: 99%